Studi Literatur Kode Etik Konseling Online - Mariana Puspa Sari; Happy Karlina Marjo (Universitas Pendidikan Mandalika, 2022)
This study aims to explain the code of ethics for online counseling by integrating information technology in guidance and counseling services. This research method is a literature study using secondary data sources collected through textbooks, e-books, scientific articles, websites, and other sources relevant to the research problem which are then analyzed descriptively. The result of this study is the rapid development of technology in various fields, which has an impact on the integration of the counseling process in the technology. Through technological intermediaries, counseling no longer has to be done face-to-face. Among the advantages and disadvantages of online counseling, the professional code of ethics for counselors still needs to be maintained. One form of supervision is supervision. Counselors, both online and face-to-face counseling, are required to improve their ability to deal with counselee problems in accordance with the provisions of Permendikbud No. 111 of 2014.